2010
DOI: 10.1007/s11805-010-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Pin1 suppresses the expression and bioactivity of MMP-9 through NF-κB in colorectal carcinoma SW480 cells

Abstract: OBJECTIVE To examine the effect of Pin1 on the expression and bioactivity of MMP-9 through NF-κB in human colorectal carcinoma SW480 cells. METHODS The eukaryotic expression vector of RNA interfering (shRNA) with the Pin1 gene (pGenesil-1-PIN1) was constructed in our previous experiments and was confi rmed through sequencing. Cell motility was tested through the wound healing assay and the Boyden chamber assay. The protein levels and bioactivity of MMP-9 were tested by Western blott ing and gelatin zymography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Previous studies have established that MMP9 expression is associated with glioblastoma growth and invasion (30). Recently, it has been demonstrated that the inhibition of Pin1 in colorectal carcinoma cells decreases the level and enzymatic activity of MMP9, presumably via nuclear factor-κB signaling (13). Similarly, a reduction in MMP9 following Pin1 inhibition was observed in the present study.…”
Section: A B C D Esupporting
confidence: 87%
“…Previous studies have established that MMP9 expression is associated with glioblastoma growth and invasion (30). Recently, it has been demonstrated that the inhibition of Pin1 in colorectal carcinoma cells decreases the level and enzymatic activity of MMP9, presumably via nuclear factor-κB signaling (13). Similarly, a reduction in MMP9 following Pin1 inhibition was observed in the present study.…”
Section: A B C D Esupporting
confidence: 87%
“…Nuclear extracts (10 g) were incubated with 300 ng biotin 3 -end labeled double-strand oligonucleotide probe (GeneMark Technology Co., Ltd., Taichung, Taiwan), 2 g of poly deoxyinosinic-deoxycytidy acid (dI-dC), 1 L 50% glycerol, and 4 L 5× DNA loading dye for 30 min at room temperature. The following biotin 3 -end labeled double-strand oligonucleotide probes were used in this study: commercial consensus oligonucleotide sequence of MMP-9-NF-B (5 -TGC CCC AGT GGA ATT CCC CAG CCT TG-3 ) (Farina et al, 1999;Qin et al, 2010). Protein-DNA complexes were detected by running the samples on non-denaturing 6% (w/v) PAGE in 0.5× Tris-borate-EDTA (TBE) buffer (GeneMark Technology Co., Ltd.), transferred to positively charged nylon membranes (Millipore Corporation, Billerica, MA, USA) using a blot transfer apparatus, and then cross-linked using a Stratagene cross-linker.…”
Section: Electrophoretic Mobility-shift Assaymentioning
confidence: 99%
“…When VSMCs switch from the contractile phenotype to the proliferative migration phenotype, MMPs are secreted and inflammatory cytokines are produced to promote vascular remodeling [ 31 ]. Studies have shown that Pin1 and RBD4 interact with NF- κ B and cause increased expression of MMP genes [ 32 , 33 ]. Our study showed that juglone and JQ1 inhibited increased MMP-9 protein expression induced by high glucose, which is consistent with studies by Liang and Duan et al [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%